2016
DOI: 10.1155/2016/7978219
|View full text |Cite
|
Sign up to set email alerts
|

Oral Exposure to Atrazine Induces Oxidative Stress and Calcium Homeostasis Disruption in Spleen of Mice

Abstract: The widely used herbicide atrazine (ATR) can cause many adverse effects including immunotoxicity, but the underlying mechanisms are not fully understood. The current study investigated the role of oxidative stress and calcium homeostasis in ATR-induced immunotoxicity in mice. ATR at doses of 0, 100, 200, or 400 mg/kg body weight was administered to Balb/c mice daily for 21 days by oral gavage. The studies performed 24 hr after the final exposure showed that ATR could induce the generation of reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…The latter two were also low in the kidney tissue (66). Similar effects were noticed in mice receiving 100, 200, or 400 mg kg -1 bw of atrazine by gavage every day for 21 days (67).…”
Section: Involvement Of Oxidative Stress In Atrazine Toxicitysupporting
confidence: 67%
“…The latter two were also low in the kidney tissue (66). Similar effects were noticed in mice receiving 100, 200, or 400 mg kg -1 bw of atrazine by gavage every day for 21 days (67).…”
Section: Involvement Of Oxidative Stress In Atrazine Toxicitysupporting
confidence: 67%
“… 21 Excessive amounts of ROS can result in lasting oxidative stress and can induce cell apoptosis. 22 , 23 In addition, oxidative stress could affect normal spermatozoa production by impairing the steroidogenic capacity of the testis. 22 As we know, MDA is used as an important biomarker for examining oxidative stress, while SOD and GSH are important antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the mice were weighted and observed for any clinical symptoms, and the information was recorded by the animal care staff. Seven days after the aerosol exposure, the mice were sacrificed and lung tissue, bronchoalveolar lavage fluid (BALF), and blood samples were collected for histology and biochemical analysis, as previously described [40,42,43,[47][48][49]. The ATR dosage was chosen based on other previous studies, but for the first time, ATR was not administered by oral gavage but instead by aerosol, because there is still limited knowledge of the effects of ATR on the lungs [50][51][52].…”
Section: Experimental Design and Groupsmentioning
confidence: 99%
“…However, until today, few reports have explored the molecular mechanisms underlying ATR induction of lung problems. Some of the most accredited hypothesis that could explain the mechanism of toxicity induced by ATR is the production of reactive oxygen species (ROS) [22,[39][40][41][42][43]. In particular, some of the study results that prompted us to investigate the ways by which ATR exerts its lung toxicity were the discovery by Zhao and colleagues that ATR could induce a response activated by nuclear factor erythroid 2-related factors 2 (Nrf2); the increase in the malondialdehyde levels as well as in the activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) found by Batti et al; and finally the results by Song et al that demonstrated that ATR enhanced the apoptotic and autophagic processes [22,39,44].…”
Section: Introductionmentioning
confidence: 99%